Does Entrepreneurship Education Matter for Students’ Business Success? The Mediating Role of Entrepreneurial Mindset - Rabiatul Hariroh, Fiqih Maria; Sandi, Prasetyo Hari; Soleha, Erin; Hidayah, Zulfa Zakiatul; Zed, Etty Zuliawati (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
Over the recent past, entrepreneurship has become an increasingly popular topic. Many individuals are interested in becoming entrepreneurs and developing their businesses. However, not everyone has the skills to be a successful entrepreneur. There are several elements that can have an impact on business success, one of which is having an entrepreneurial mindset. The purpose of this paper is to determine the role of entrepreneurial mindset in mediating entrepreneurship education on student business success. The research data used is primary data by distributing questionnaires to respondents. The population in this study were students of the Faculty of Economics and Business Sciences, Pelita Bangsa University. The sample in this study was using Non-Probability Sampling. The sample used in this study were 100 respondents using the nonprobability sampling method, namely accidental sampling, which is a sampling technique based on chance, anyone who by chance / incidentally meets the researcher can be used as a sample if it is deemed that the person who happened to be met is suitable as a data source. In this study, the data analysis techniques used were descriptive analysis techniques and inferential analysis techniques using Partial Least Square (PLS) analyzers. According to the research results, entrepreneurship education and entrepreneurial mindset significantly affect students' business success.